Adaptive single-phase/three-phase reclosing scheme for transmission lines in passive network supplied by MMC-HVDC. (December 2019) - Wang, Ting; Hussain, Kazmi Sayed Tassawar; Song, Guobing; Han, Wei; Liu, Chao
Highlights: An active fault identification method for passive networks supplied by MMC-HVDC. The active injection utilized for both adaptive single/three phase auto-reclosing scheme. Application to single-circuit and multi-circuit transmission lines. Repeated injections and extra independent assessments can be supplemented to prevent misjudgement. Abstract: Modular multilevel converter (MMC) shows prominent advantages on supplying passive networks, which are usually classified by power supply shortage and relatively weak structure. In order to reduce the unnecessary outage time and improve the system stability, an adaptive ac auto-reclosing scheme for passive networks is proposed based on characteristic signal injection. Additional MMC controller is designed to inject the characteristic signals into the healthy line, which in turn induces corresponding signals to the faulty line. Then fault properties are assessed by the travelling wave based fault location method. Finally, an adaptive auto-reclosing scheme is proposed to shorten the reclosing time and avoid the second fault shock to a large extent. The proposed scheme could be applied for both single-circuit and multi-circuit transmission lines. The simulation results obtained from PSCAD/EMTDC verify the effectiveness of the proposed method.